Volcanic and sedimentary rocks reveal the Paleozoic tectonic evolution of the Lhasa Terrane, Tibet - He, Qing; Lang, Xinghai; Wang, Xuhui; Deng, Yulin; Xie, Fuwei; Scott, James M.; Lou, Yuming (International Geology Review, 2022)
The central Lhasa Terrane preserves the geological record of the opening, subduction, and closure of the Paleo-Tethys Ocean. However, the early tectonic history of the Paleo-Tethys Ocean remains unclear. Here, we present the results of a systematic study of Paleozoic volcanic-sedimentary rocks of the central Lhasa Terrane. The composition of Paleozoic sandstone includes quartz, potassium feldspar, plagioclase, lithic fragments, and a small amount of sericite. Qt-Ft-Lt Dickinson ternary diagrams reveal that the Paleozoic succession includes feldspatho-litho-quartzose sandstone (Gangsangmu and Yongzhu formations), litho-feldspatho-quartzose sandstone (Lower Laigu and Lower Laga formations), litho-quartzo-feldspathic sandstone (Upper Laigu and Upper Laga formations), and quartzo-litho-feldspathic sandstone (Luobadui formation). The Late Ordovician Gangsangmu formation shows passive margin characteristics controlled by sediment recycling. The Early Carboniferous-Late Carboniferous Yongzhu formation is derived from an evolved arc. The Late Carboniferous Lower Laigu and Lower Laga formations were associated with a passive margin controlled by sediment recycling. The Early Permian (Upper Laga, Upper Laigu, and Luobadui formations) represent active continental margin sedimentary rocks. The Early Permian volcanic rocks (287 similar to 274 Ma) belong to the calc-alkaline-potassic /shoshonitic series with high positive epsilon(Hf)(t) values. The Early Permian volcanic rocks have high LREE and LILE (e.g. Rb, Sr), and are depleted in HREE and HFSE (e.g. Nb and Ta, Ti), which indicate a subduction-related arc setting. Our findings, combined with previous studies, show that the northern margin of Gondwana was passive in the Late Ordovician. In the Early Carboniferous, a back-arc basin formed on this northern margin due to the subduction of the Paleo-Tethys Ocean. In the Late Carboniferous, the Sumdo Paleo-Tethys Ocean opened, and the southern edge of the central Lhasa Terrane was a passive margin. In the Early Permian, the Sumdo Paleo-Tethys Ocean began its initial northward subducted and formed the arc volcanic rocks on the central Lhasa Terrane.
CRIS-Team WoS Importer:2022-10-21